HUBUNGAN TINGKAT KEBERDAYAAN DENGAN TINGKAT KEMANDIRIAN ANGGOTA KELOMPOKTANI PROGRAM SISTEM PERTANIAN TERPADU (SPT) PT. RAPP DI KABUPATEN SIAK - Hervika Nova Nadap-Dap; Roza Yulida; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research are: 1) Assessing the level of empowerment program members of farmer groups Integrated Farming Systems PT. RAPP in Siak, 2) Assess the degree of independence of members of farmers program Integrated Farming Systems PT. RAPP in Siak, 3) Knowing the empowerment level relationship with the level of independence of farmers program Integrated Farming Systems PT. RAPP in Siak. This study was conducted in Siak district, which includes three sub-districts right kerinci, District and Sub-District Dayun River Apit starting from September 2015 to January 2017. The determination of sampling determined by purposive sampling with the consideration that the farmer who made the respondent is a member of the built members of farmer groups PT. RAPP program received Integrated Agricultural Systems, members of farmer groups most active members, assistance programs Integrated Farming System representing all farmer groups. The number of respondents as many as 30 people. The analysis using Likert scale and Rank Spearman correlation analysis. The results of this study show that: 1) The level of empowerment members of farmer groups in the program Integrated Farming Systems Siak Regency included in the category of Most Powerful. 2) The level of independence of members of farmer groups in Siak program Integrated Farming Systems included in the High category. 3) Relationship level of empowerment to the level of independence of members of farmers Integrated Farming Systems program showed a positive correlation (Unidirectional). This suggests that when the members of the degree of independence helpless farmer group members is also high. Keywords: empowerment, self-reliance, Integrated Farming System, Farmers